COMPARISON OF DENTAL EXTRACTION ANXIETY AND DEPRESSION BETWEEN YOUNG AND OLDER ADULTS - GHAURI , MQK; HUSSAIN , S; IQBAL , Z; JAVED , I; DIN , AL; NAND , A; SYED , S; AVINASH, . (Biological and Clinical Sciences Research Journal, 2024)
Dental anxiety and depression represent significant psychological factors that can influence an individual's willingness to seek and undergo dental treatments, including routine procedures such as dental extractions. The main objective of the study is to find the comparison of dental extraction anxiety and depression in young adults as compared to older adults. This cross-sectional study was conducted in Karachi from January 2023 to November 2023. Data was collected from 320 participants in two age groups: young and older adults. Young adults age 8-35 years and older adults 60 years and above. Demographic information, including age, gender, education level, and dental history, was gathered alongside clinical details such as the type and complexity of dental extractions. Validated scales, notably the Modified Dental Anxiety Scale (MDAS) for dental anxiety and the Patient Health Questionnaire-9 (PHQ-9) for depression were employed for assessment. Data were collected from 320 participants. Approximately 36% of the population is estimated to be affected by dental anxiety, with 10 to 20% experiencing extreme levels. The mean Modified Dental Anxiety Scale (MDAS) scores differed significantly between age groups, with young adults having a mean score of 16.2 (SD=4.5) compared to older adults with a mean score of 14.5 (SD=3.8) (p<0.05). Similarly, the mean Patient Health Questionnaire-9 (PHQ-9) scores varied significantly between age groups, showing that young adults had a higher mean score of 8.3 (SD=3.2) compared to older adults with a mean score of 6.7 (SD=2.8) (p<0.01). It is concluded that gender and educational influences further emphasize the need for personalized approaches in dental care. Tooth extraction anxiety and depression are common in older adults. These insights highlight the potential for integrating mental health considerations into routine dental practices, fostering more patient-centered and age-specific interventions to enhance oral health and well-being.